Bioavailability of Two Dermal Formulations of S(+)Ibuprofen in Rabbit - González-Peńas, Elena; Echeverría, Hugo Carlos; Mosqueraa, Javier; Esteras, Antonio; Bruseghinic, Leo (Arzneimittelforschung, 2003)
Ibuprofen (CAS 15687-27-1) is widely used in painful situations and, usually, is administered in the racemic form. Since enantiomers may exert different pharmacodinamic and pharmacokinetic effects, the pharmaceutical industry has placed new emphasis on the preparation of new formulations of enantiomerically pure drugs that must be pharmacokinetically characterised prior to their administration in human beings. In this study, the absorption kinetics of two topical formulations of S(+)ibuprofen in rabbits was investigated. The S(+)ibuprofen levels in rabbit plasma were determined by a non-chiral HPLC method, whereas the absence of the R(-)ibuprofen enanti-omer in plasma was confirmed by a chiral HPLC method. The results showed that S(+)ibuprofen was absorbed through the rabbit skin upon administration and the obtained levels varied with the formulation.
Keywords: Anti-inflammatory drugs, non-steroidal; CAS 15687-27-1; Ibuprofen, bioavailavility, S(+) enantiomer, topical administration